The use of the pMAL-c2 expression system for the production of human cytochrome P450c17 - Roux, Stephan P.(Stephan Petrus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.